Pendidikan Karakter Bersahabat dan Cinta Damai Perspektif Syeikh Muhammad Syakir dalam Kitab Waṣōyā Al-Ābā’i Lil Abnā’i dan Relevensinya Terhadap Pendidikan Dasar - Rohmah, Nuri Fadlilatur; Nurfalah, Yasin (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
Negative behavior such as bullying shows the fragility of character in educational institutions. Discussions and studies about solutions to moral decadence are increasingly being discussed. One of the authors offers an education on friendship/communicative and peace-loving characteristics from Shaykh Muhammad Syakir which is then relevant to basic education. With the problem statement (1) What is Muhammad Syakir's perspective on character/communicative and peace-loving education in the Book of Waṣōyā Al-Ābā'i Lil Abnā'i? (2) What is its relevance to basic education? The type of research used is library research which is qualitative in nature, with an approach using hermeneutics. The results of the research are: (1) Material about friendly/communicative and peace-loving character education in the book Waṣōyā Al-Ābā'i Lil Abnā'i by Syaih Muhammad Syakir, namely a. communication with friends b. communication in learning and discussion c. communication in meetings/majlis d. social etiquette (2) There is relevance between the values of friendly/communicative character education and love of peace contained in the book Waṣōyā Al-Ābā'i Lil-Abnā'i with character education in basic education.